Tropospheric SO2 and NO2 in 2012–2018: Contrasting views of two sensors (OMI and OMPS) from space. (15th February 2020) - Wang, Yi; Wang, Jun
Abstract: The global long-term Climate Data Records (CDRs) of atmospheric SO2 and NO2 have been obtained from multiple satellite sensors since 1990s, and all these CDRs show consistently decreasing trends in developed countries and increasing trends in developing countries prior to 2010. However, much less clear is the quantitative differences among these CDRs and how such differences affect the inferences for atmospheric SO2 and NO2 climatology in terms of their annual means as well as their frequency distributions. Here, we compare and contrast the CDRs from the aged OMI sensor (the flagship for measuring NO2 and SO2 since 2005) and the young OMPS sensor series (that started measuring NO2 and SO2 in 2012 and will continue in next 2-3 decades). We show that after 2012, the difference of average SO2 between OMPS and OMI is 0.12 DU and it only decreases to 0.04 DU after bias correction, despite their consistence in spatial pattern. NO2 CDRs from OMPS and OMI overall exhibit general agreement in both magnitude and spatial pattern. Furthermore, the CDR differences can lead to the opposite trend signs in developed countries and the difficulty to reconcile trend magnitude in developing countries. Notable consistence in trend signs does exist, regardless of radiative cloud fraction, mainly showing decline of SO2 and NO2 in China and increasing in India; much inconsistence is, however, found in many parts of developed countries. No SO2 trends and inconsistent NO2 trends are found over Europe, and notable differences are found over U.S. where OMI SO2 and NO2 's declining trends are consistent with surface observations, but OMPS SO2, albeit its better spatial agreement with surface data, shows increasing trend. This study calls the importance to assess CDRs from different satellite sensors with the account of frequency distributions for extreme events. This importance is emergent as the atmospheric SO2 and NO2 amounts are closer to the uncertainties of satellite-based retrievals in developed countries and are or will be declining in developing countries in the coming decades, all of which make the detection of signs, magnitudes, and spatiotemporal dichotomy a challenge from space. Highlights: SO2 and NO2 trends and frequency distributions from OMPS and OMI are compared. Qualitatively consistent for upward trend in China and downward trend in India. Quantitative differences in trend and sign exist in developed countries. SO2 and NO2 signals for remote sensing are weakening in many parts of world. Reconciling OMI and OMPS product differences is emergently important.